2015
DOI: 10.4317/jced.51764
|View full text |Cite
|
Sign up to set email alerts
|

Oral mucosal diseases in anxiety and depression patients: Hospital based observational study from south India

Abstract: Objectives: The objective of this study was to evaluate the prevalence of different Oral Mucosal diseases in Anxiety and Depression patients. Material and Methods: A hospital based observational Study was conducted in the department of Psychiatry and department of Oral Medicine and Radiology. Patients who were diagnosed with Anxiety or Depression by the psychiatrists using Hamilton Anxiety and Depression scale were subjected to complete oral examination to check for oral diseases like Oral Lichen Planus (OLP),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
31
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(38 citation statements)
references
References 19 publications
(27 reference statements)
3
31
0
4
Order By: Relevance
“…Wilson's original description of LP already included the presence of hysteria, anxiety and depression as aetiological factors. Since then, many authors have demonstrated the importance of these psychological factors in the onset and development of the disease (Adamo et al, 2015;Alves et al, 2015;Čanković et al, 2015;Kalkur, Sattur, & Guttal, 2015;Sandhu et al, 2014;Suresh et al, 2015;Valter et al, 2013). Our results are similar to previous ones, considering that the HADS test showed higher levels of anxiety and depression among the OLP group patients than among the members of the control group.…”
Section: Discussionmentioning
confidence: 99%
“…Wilson's original description of LP already included the presence of hysteria, anxiety and depression as aetiological factors. Since then, many authors have demonstrated the importance of these psychological factors in the onset and development of the disease (Adamo et al, 2015;Alves et al, 2015;Čanković et al, 2015;Kalkur, Sattur, & Guttal, 2015;Sandhu et al, 2014;Suresh et al, 2015;Valter et al, 2013). Our results are similar to previous ones, considering that the HADS test showed higher levels of anxiety and depression among the OLP group patients than among the members of the control group.…”
Section: Discussionmentioning
confidence: 99%
“…Patients enrolled in the present study were admitted for the first time to the microvascular disorder clinic at an angiology center, presenting with symptoms of PRP as defined by the LeRoy and Medsger criteria. 1 A total of 61 patients met the study criteria: 42 women and 19 men at a median age of 24 years (interquartile range [IQR,[20][21][22][23][24][25][26][27], and capillary flow was measured using LDF on the oral mucosa, teeth, and lower lip vermilion (TABLE 1). 1,17 At the same time, the temperature of the oral mucosa was measured.…”
Section: Methodsmentioning
confidence: 99%
“…The result of Suresh et al study showed patients with severe anxiety who experienced BMS was 75%, moderate anxiety was 25%, and no patient with mild anxiety [5]. Anxiety can cause changes in the oral cavity [6]. Increased levels of anxiety can worsen body condition including oral cavity [2].…”
Section: Advances In Health Science Research Volumementioning
confidence: 99%
“…Anxiety can cause pathological changes in the body including the oral cavity [5].Oral lichen planus (OLP), recurrent aphthous stomatitis (RAS), and burning mouth syndrome (BMS) can be affected by anxiety [5,6].…”
Section: Introductionmentioning
confidence: 99%